2018
DOI: 10.1021/acssuschemeng.8b03685
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Ethane and Ethylene over 3D-Printed Ethane-Selective Monoliths

Abstract: The use of paraffin-selective adsorbents in separation of paraffin/olefin pairs has been recently demonstrated as a sustainable platform for recovering a highly pure olefin product directly from the adsorption step. These materials allow for development of a less expensive and economically attractive technology for olefin/paraffin separation. Herein, we report formulation of paraffin-selective adsorbents into monolithic contactors and evaluation of their adsorptive performance in ethane/ethylene separation. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 45 publications
4
47
0
Order By: Relevance
“…Thakkar et al reported the 3D-printing of MOF, embedded in an organic-inorganic binder for removal of CO 2 from air, 15 as well as the 3D-printing of ZIF-7 embedded within organic monoliths for ethane/ethylene separation processes. 16 Our group reported the 3D-printing of Cu-BTC MOF for the adsorption of organic dyes from solutions, 17 and Lyu et al reported a 3D-printed cobalt-based MOF embedded within an organic binder for energy storage applications. 18 More examples on 3D-printed MOFs were explored by Lawson et al and Sultan et al 19,20 Recently, our group, in collaboration with Amo-Ochoa and Zamora, also published the 3D-printing of a Cu 2+ coordination polymer for the colorimetric sensing of humidity and water.…”
Section: Introductionmentioning
confidence: 98%
“…Thakkar et al reported the 3D-printing of MOF, embedded in an organic-inorganic binder for removal of CO 2 from air, 15 as well as the 3D-printing of ZIF-7 embedded within organic monoliths for ethane/ethylene separation processes. 16 Our group reported the 3D-printing of Cu-BTC MOF for the adsorption of organic dyes from solutions, 17 and Lyu et al reported a 3D-printed cobalt-based MOF embedded within an organic binder for energy storage applications. 18 More examples on 3D-printed MOFs were explored by Lawson et al and Sultan et al 19,20 Recently, our group, in collaboration with Amo-Ochoa and Zamora, also published the 3D-printing of a Cu 2+ coordination polymer for the colorimetric sensing of humidity and water.…”
Section: Introductionmentioning
confidence: 98%
“…Their possible use on an industrial scale implies transformation into monoliths to improve the performance compared with that of traditional bead or pellet forms, allowing separations at lower pressures or temperatures. Thakkar et al [44b] . used DIW to 3D print these materials by dissolving Ni‐BT in ethanol at 60 °C, 2 h, and PVA in DMSO was slowly added to this solution.…”
Section: Three‐dimensional Printed Materials Based On Coordination Bomentioning
confidence: 99%
“…In the latter case, the ZIF‐7 powder took 15 min to reach the same degree of saturation. ZIF‐7‐M presents stronger interactions with the adsorbed gases due to higher adsorption heats [44b] …”
Section: Applicationsmentioning
confidence: 99%
“…8,9 From this perspective, metal-organic frameworks (MOFs) are promising filler candidates. [10][11][12][13][14][15] Conceptually, the integration of a MOF component into additive formulations has been approached and then realized through different 3D printing techniques 4 -inkjet, 16,17 direct ink writing (DIW), [18][19][20][21][22][23][24][25][26][27] fused deposition modelling (FDM), [28][29][30] digital light processing (DLP) 31 and selective laser sintering (SLS). 32,33 For instance, photoluminescent lanthanide MOFs-based inks for inkjet printing were reported by da Luz et al 16 In addition to examples of MOF coatings grown on 3D printed objects obtained by stereolithography (SLA) 34 or direct ink writing, 24 fabrication of monoliths with full integration of the MOF component within a melting matrix of acrylonitrile butadiene styrene (ABS), 28,29 poly(lactic acid) (PLA) or polyurethane (TPU) thermoplastics 30 have been achieved using fused deposition modelling.…”
Section: Introductionmentioning
confidence: 99%
“…28 Unlike in the FDM approach, firm monoliths with accessible internal porosity, suitable for applications involving adsorption, have been obtained via direct ink writing. Moreover, several representative examples of composites with high MOF loading 22 suitable for gas separation, 18,20,21 catalysis, 26 molecule sequestration and release have been reported. 19,25 Similarly, tailored shapes with †Electronic Supplementary Information (ESI) available: Chemical schemes of commercial oligomers; tables with inks formulation composition; DLP 3D printed details and specifications; additional figures; N 2 and Ar adsorption data and plots; TEM images and particle size distribution histograms; NMR data and plots; FTIR; viscosity data; ATR-IR, kinetic data of photopolymerization in systems with and without MOF additive; Raman spectra and mapping; mechanical data; optic microscope images; SEM-EDX maps; data on degree of crosslinking; TG and DSC analyses; gas separation performance data.…”
Section: Introductionmentioning
confidence: 99%